326 Effects of local laser treatment on vulvovaginal atrophy for women with breast cancer: a prospective study with long-term follow-up. (4th December 2020) - Veron, Lucie; Wehrer, Delphine; Annerose-Zephir, Gisèle; Chaltiel, Dan; Delaloge, Suzette; Pistilli, Barbara; Pautier, Patricia
Abstract : Introduction/Background: Women with breast cancer (BC) often suffer from severe vulvovaginal atrophy (VVA) linked to endocrine deprivation, which is worsened by BC treatments and ultimately leads to urinary symptoms, dyspareunia and poor sexual quality of life. Treatment side effects, including gynaecological side effects, could affect adherence to treatment, such as endocrine therapy. We conducted a prospective study on women with BC to evaluate the effect of fractional microablative CO2 laser therapy on VVA in the long term. Methodology: Women with a history of BC, without contra-indication to laser therapy and suffering from VVA were proposed to have fractional microablative CO2 laser therapy (MonaLisaTouch®, DEKA) once per month for 3 months. Vaginal health was objectively determined with pH level and trophicity on pap smear. Sexual and urinary quality of life status were assessed using the Female Sexual Function Index (FSFI) score and the Ditrovie score. Measurements were performed at baseline and 6 months. Quality life scores were also assessed about 18 months after the last laser session. Paired statistical tests between baseline and 6 months and between baseline and end of study were computed using R software (version 4.0.2). Results: 46 women with BC (median age [interquartile range] = 56.5 [47.0 – 59.4]) were treated between May and December 2018, of whom 36 were taking endocrine therapy (tamoxifen n=6, aromatase inhibitors ± LHRH agonist n=30). pH level slightly decreased over time (mean = 6.5 (SD 0.9) at baseline versus 6.4 (SD 0.9) at 6 months, p=0.02) whereas trophicity on pap smear did not change. Sexual quality of life was significantly improved at 6 months and at the end of study (mean = 11.3 (SD 7.5) at baseline versus 19.4 (SD 6.7) (p<0.0001) and 15.2 (SD 9.0) (p=0.009)). Ditrovie total score improved at 6 months (mean = 1.05 (SD 0.5) versus 1.2 (SD 0.6) at baseline, p=0.01) but not at the end of study. About 56% of treated women asked for a maintenance laser session at the end of the study. Conclusion: Our data show that fractional microablative CO2 laser is effective for women with BC on VVA's symptoms and gynaecological quality of life. Effects are long-lasting but decrease after a certain time suggesting that maintenance sessions might be necessary. More research has yet to be done on treatment schedule for women with BC, such as number of laser sessions at initiation (3 or 4) and duration before maintenance sessions. Disclosures he microablative laser was provided by DEKA. There was no financial support from DEKA.